Analysis of the Quality of Student Administration Services at SMK PGRI Enrekang - Nasaruddin Hasyim; Muhammad Fadli; Haedar Akib (Journal of Social Science and Economics (JOSSE), 2024)
Student administration plays an important role in the implementation of school activities to run effectively and efficiently. This study aims to determine the quality of student administration services at SMK PGRI Enrekang. This study is a qualitative descriptive study. The informants in this study were the Head of Administration, Teachers, and Students. Data collection techniques through observation, interview, and documentation methods. Data analysis techniques use data collection techniques, condensation, data presentation, and drawing conclusions. The results of the study indicate that the quality of student administration services at SMK PGRI Enrekang is in the "quality" category, which can be seen in each dimension, namely: Tangible is quite good, seen from the appearance of the administrative staff who are neat and polite according to school regulations, the administration room is equipped with facilities such as photocopiers, printers, computers, and air conditioning. However, it is still constrained by the narrow condition of the administration room. The Reability dimension is reliable, seen from the accuracy of the administrative staff in providing services and the ability of employees to use assistive devices. The Responsiviness dimension is responsive, seen from the speed and accuracy of the administrative staff in serving students. The Assurance dimension is good, seen from the administrative staff providing certainty of time in the service process. The Empathy dimension is good, seen from the attitude of the administrative staff who are friendly, polite, and do not discriminate against students in providing services.